Developing a framework for best practices of governance of State Statutory Bodies (SSB) in Sarawak / Ambrose Anak Dango - Dango, Ambrose (Institute of Graduate Studies, UiTM, 2015)
According to Chief Minister Department report (2008) the total number of public complaints on poor level of services received by State Statutory Bodies in Sarawak increased to 629 in 2007 as compared to 520 in 2006. This is one clear evidence that the State Statutory Bodies have not been able to deliver the level of services up to the expectation of the customers and stakeholders in Sarawak due to unsatisfactory governance. This problem is being corroborated by the finding in the Auditor-General report on State Statutory Bodies in Sarawak (2010 and 2011). The Sarawak government is responsible to fulfill the needs, hope and aspiration of its citizen with limited resources available through best practices of governance. The main objective of this study is to evaluate the best practices of governance and its effects on the level of services in State Statutory Bodies in Sarawak. These best practices of governance were based on literature reviews from developed and developing countries and from the experiences of State Statutory Bodies in Sarawak. The level of services refers to the quality of services given by State Statutory Bodies to its stakeholders and the level of services are evaluated by survey questionnaire and interviews. Hence, the specific objectives of this study are to identify factors in best practices of governance for State Statutory Bodies in Sarawak, the predictor in best practices of governance and to recommend a framework of best practices of governance that can assist State Statutory Bodies in Sarawak.The comprehensive and extensive literature reviews on governance in the public sector in developing and developed countries clearly show the existence of factors in best practices of governance in the public sector. This finding is back up by the empirical evidence and findings obtained through questionnaires survey and rigorous data analysis of this study. An analysis on the feedback and recommendations from the openended questions further reinforce the existence of best practices of governance in State Statutory Bodies and its correlation to the level of services provided by State Statutory Bodies to its customers and stakeholders…